Patient satisfaction and operator proficiency in gasless transaxillary endoscopic thyroidectomy under IONM: a retrospective cohort study - Zhang, Yushuai; Zhao, Yishen; Tang, Hong; Zou, Hongrui; Li, Yang; Bian, Xuehai (Frontiers in Endocrinology, 2024)
Background: This study aims to evaluate the surgical safety and effectiveness of gasless transaxillary endoscopic thyroidectomy (GTET), assess patients' short-term perceptions and long-term outcomes, and delineate the learning curve and key surgical techniques of the operators.Materials and Methods: Clinicopathological and postoperative follow-up data from patients with unilateral thyroid cancer in the same period were collected. These patients were divided into the GTET group and the traditional open surgery group to compare and analyze the differences and explore the factors affecting the learning curve of GTET.Results: Patients who chose GTET had better general health and thyroid conditions than those in the open group, and the quality of postoperative life was better in the GTET group than in the open group, with the main differences between the two groups being appearance and neck and shoulder function. The GTET learning curve in this study peaked at 19 cases, with slight differences between left and right, and a larger sample size is still needed to explore the factors affecting the learning curve.Conclusions: GTET has a reliable safety and efficacy profile for patients with unilateral thyroid cancer. Intraoperative nerve monitoring (IONM) techniques require some adaptation in GTET. In some respects, patients' postoperative experience and quality of life are superior to those of conventional open surgery. There is a learning curve for GTET, but large samples are still needed to explore its true significance.